2020
DOI: 10.1002/nem.2124
|View full text |Cite
|
Sign up to set email alerts
|

VNF‐Consensus: A virtual network function for maintaining a consistent distributed software‐defined network control plane

Abstract: Software-defined networks (SDN) usually rely on a centralized controller, which has limited availability and scalability by definition. Although a solution is to employ a distributed control plane, the main issue with this approach is how to maintain the consistency among multiple controllers. Consistency should be achieved with as low impact on network performance as possible and should be transparent for controllers, without requiring any change of the SDN protocols. In this work, we propose VNF-Consensus, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
9
0
2
Order By: Relevance
“…In this scheme, the controller could perform its control plane activities without the high consumption tasks required to maintain consistency. The experimental results showed that this scheme could effectively reduce costs and improve the actual benefits, especially in low controller overhead [14]. Hu and Liu reported that the Raft consistency algorithm was one of the typical consistency algorithms in distributed systems to manage the consistency of log replication.…”
Section: Related Workmentioning
confidence: 97%
“…In this scheme, the controller could perform its control plane activities without the high consumption tasks required to maintain consistency. The experimental results showed that this scheme could effectively reduce costs and improve the actual benefits, especially in low controller overhead [14]. Hu and Liu reported that the Raft consistency algorithm was one of the typical consistency algorithms in distributed systems to manage the consistency of log replication.…”
Section: Related Workmentioning
confidence: 97%
“…As early as 2015 (Turchetti and Duarte, 2015), an NFV-COIN service was implemented based on the classic failure detectors of distributed systems; that work was later expanded (Turchetti and Duarte Jr, 2017). Consensus was another distributed service implemented with NFV-COIN (Venâncio et al, 2021), used to maintain the consistency of a group of SDN (Software-Defined Networks) controllers. In yet another effort, the network was augmented with the ability to natively offer reliable and ordered broadcast services (Venâncio et al, 2019).…”
Section: Nfv-based Network Traditional Networkmentioning
confidence: 99%
“…Existing solutions employ the controllers themselves to perform the synchronization tasks, or alternatively synchronize the data plane. In (Venâncio et al, 2021) the VNF-Consensus service is proposed to implement the Paxos consensus algorithm and to maintain the consistency of a distributed control plane that consists of multiple SDN controllers. VNF-Consensus does not require any modification of the data plane or the SDN protocol (in this case, again OpenFlow).…”
Section: Consensus As An Nfv-coin Service: Vnf-consensusmentioning
confidence: 99%
“…Considerando funcionalidades para tolerância a falhas em redes SDN,é possível observar diversos outros trabalhos que incluem a sincronização consistente no plano de controle distribuído. Estas funcionalidades se traduzem em diferentes algoritmos, tais como: Paxos [Ho et al 2016, Venâncio et al 2018, Replicação de Máquina de Estados [Canini et al 2015, Mahajan et al 2016, Zookeeper [Koponen et al 2010], Raft [Medved et al 2014], entre outros algoritmos frequentemente empregados no contexto de tolerância a falhas em sistemas distribuídos. Também são encontradas soluções que procuram garantir a execução consistente do plano de dados.…”
Section: Trabalhos Relacionadosunclassified
“…Em uma rede SDN o controlador executa um papel fundamental. Por este motivo, pode-se observar diversos esforços concentrados no controlador no sentido de avaliar seu desempenho [Zulu et al 2018], torná-lo distribuído [Kohler et al 2018], escalável [Bianco et al 2017, Karakus andDurresi 2017], confiável [Curic et al 2018, Venâncio et al 2018, seguro e tolerante a falhas [Gonzalez et al 2016]. Estes atributos foram ou estão sendo implementados nos diversos controladores disponíveis para uso.…”
Section: Introductionunclassified